AN EFFECTIVE RISK-PREVENTIVE MODEL PROPOSAL FOR OCCUPATIONAL ACCIDENTS AT SHIPYARDS - Acuner, Ozge; Cebi, Selcuk (BRODARSKI INST, 2016)
According to the statistics of occupational accidents, it is observed that the number of accidents occurred in shipbuilding industry is high and the rate of deaths and serious injuries among these accidents is higher than in other industries. However, the number of the studies to prevent these accidents in both industrial and scientific practices is considerably low. Therefore, the objective of this study is to develop an efficient risk preventive model in accordance with occupational health and safety regulations for industrial organizations. The approach proposed in this study differs from those described in the literature, because it is based on fuzzy set theory in order to cope with uncertainties on probability and severity definitions in terms of occupational health and safety. Furthermore, in this paper, risk severity is considered in terms of harm to worker, harm to environment, and harm to hardware, whereas in the literature, risk severity is generally considered solely in terms of only harm to worker. Then, risk magnitude is obtained by utilizing fuzzy inference system. The proposed approach is applied to a shipyard located in the Marmara Region in order to illustrate the applicability of the model.
Keywords: occupational safety and health; shipyard's work process; risk assessment and analysis; accident prevention; WORKERS; SAFETY; TURKEY; FATALITIES; INDUSTRY; Engineering